2023
DOI: 10.1002/jcp.30976
|View full text |Cite
|
Sign up to set email alerts
|

Tight junctions and acute kidney injury

Abstract: Acute kidney injury (AKI) is characterized by a rapid reduction in kidney function caused by various etiologies. Tubular epithelial cell dysregulation plays a pivotal role in the pathogenesis of AKI. Tight junction (TJ) is the major molecular structure that connects adjacent epithelial cells and is critical in maintaining barrier function and determining the permeability of epithelia. TJ proteins are dysregulated in various types of AKI, and some reno‐protective drugs can reverse TJ changes caused by insult. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Mass spectrometry analysis of renal tissue proteins collected from patients with IgAN in our previous study revealed that the expression of TJP1 was significantly lower in the IgAN group than in the normal control group ( 27 ). Within renal tissues, TJP1 is mainly expressed in podocytes, proximal tubules, distal convoluted tubules, and collecting ducts ( 32 ). Tight junctions are key structures that anchor adjacent tubular epithelial cells, an essential interaction for the maintenance of tubular barrier integrity ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry analysis of renal tissue proteins collected from patients with IgAN in our previous study revealed that the expression of TJP1 was significantly lower in the IgAN group than in the normal control group ( 27 ). Within renal tissues, TJP1 is mainly expressed in podocytes, proximal tubules, distal convoluted tubules, and collecting ducts ( 32 ). Tight junctions are key structures that anchor adjacent tubular epithelial cells, an essential interaction for the maintenance of tubular barrier integrity ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within renal tissues, TJP1 is mainly expressed in podocytes, proximal tubules, distal convoluted tubules, and collecting ducts ( 32 ). Tight junctions are key structures that anchor adjacent tubular epithelial cells, an essential interaction for the maintenance of tubular barrier integrity ( 32 ). Abnormal expression of tight junction proteins is associated with acute kidney injury, and restoration of tight junction protein expression through various mechanisms can alleviate the renal dysfunction involved in acute kidney injury ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Occludin and claudins are two essential transmembrane proteins that make up TJs, together with the ZO protein family, and form scaffolds [ 32 ]. The loss or enrichment of tight junction proteins is closely associated with various pathological conditions [ 33 , 34 , 35 ]. Claudin-1 regulates paracellular permeability, and its overexpression improves barrier function [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI), previously referred to as acute renal failure (ARF), is characterized by a sudden and rapid decline in kidney function or kidney damage that occurs within a short timeframe 1) . AKI is diagnosed based on elevated serum creatinine levels (a marker of kidney excretory function) and decreased urinary output (a quantitative indicator of urine production) within 7 days, as defined by the Kidney Disease Improving Global Outcomes (KDIGO) criteria 2) .…”
Section: Introductionmentioning
confidence: 99%